Variance components estimation for type traits in Slovenian Brown Swiss cattle - Špehar, Marija (Acta agriculturae Slovenica, 2012)
The objective of this study was to estimate genetic parameters for 39 (26 official and 13 new) scored type traits in Slovenian Brown Swiss cattle. Data set included records of 35 386 Brown Swiss cows scored from 2000 to 2011 using method 'System 97'. The studied type traits were scored on scale from 1 to 9 (29 traits), measured by stick or tape (five traits) or expressed in points from 60 to 90 (five traits). Multiple-trait analyses based on three models were used for estimates of genetic parameters. Fixed class effects in the models were: classifier and year of scoring interaction, calving season, and time from calving to scoring. Bodz condition score effect was additionally fitted as linear regression in the second model. The third model included time after milking as fixed class effect instead of condition. Direct additive genetic effect and herd were used in the models as random effects. Estimated heritabilities ranged from 0.13 to 0.46 for frame and from 0.03 to 0.22 for form traits. Low to intermediate heritabilities (from 0.10 to 0.25) were estimated for mammary system traits. The lowest heritability estimates, in range from 0.04 to 0.13, were obtained for foot and leg traits. The variance ratio for herd covered between 0.02 and 0.26 of phenotypic variation. Genetic correlations among type traits ranged from -0.41 between rear legs side view and legs overall to 0.99 between rump height measured by tape and rump height linearly scored for frame traits. High genetic correlations were estimated for the following pairs of traits: rump width measured and rump width linearly scored (0.92), central ligament and central ligament redefined (0.97), body depth measured and body depth linearly scored (0.86). Phenotypic correlations between pairs of traits were similar in direction but smaller in magnitude in comparison to genetic correlations. Measured type traits should be replaced with the scored one since genetic correlations between them were high. The replacement will lead to the same efficient but cheaper scoring system.
Keywords: cattle; govedo; breeding; pasme; rjava pasma; Brown Swiss; type trais; lastnosti zunanjosti; heritability; dednostni delež; genetic correlations; genetske korelacije